Timing calibration and directional reconstruction for Tunka-HiSCORE. (July 2015) - Porelli, A; Bogorodskii, D; Brückner, M; Budnev, N; Chvalaev, O; Dyachok, A; Epimakhov, S; Eremin, T; Gress, O; Gress, T; Horns, D; Ivanova, A; et al.
Abstract: The Tunka-HiSCORE detector follows the concept of a non-imaging wide-angle EAS Cherenkov array, designed to search for γ-ray sources above 10 TeV and to investigate the spectrum and composition of cosmic-rays above 100 TeV. A prototype array with 9 stations has been deployed in October 2013 at the site of the Tunka experiment in Russia. We describe design and performance of the array data acquisition system DAQ-2, focusing on its timing system based on the White Rabbit technology for sub-nsec time-synchronization over ethernet. First results of EAS arrival direction reconstruction, compared with MC simulations, and tests with artifical light sources verify an excellent performance of the system.